Human Capital Strategic Initiative in Creating Value of Competency Dictionary at PT. United Tractors (Tbk) - Sujaya, Gina Mayasari; Gustomo, Aurik (The Indonesian Journal of Business Administration, 2013)
United Tractors excellence in developing the company's business can be seen from the number of awards earned United Tractor, one of which is the acquisition of the award for Best Corporate Transformation in Indonesia in 2012. Business transformation made United Tractors done by sticking to two goals there are economic value creation and the creation of organizational capabilities. In the creation of this organization capabilities, United Tractors attaches importance to the development of employees in the company's capabilities. One of the Human Capital strategy is performed at the end of 2012 is to develop a competency dictionary company, which insists on changing Business Management Competency (BMC) in the enterprise business process. Competency dictionary value creation would need to be based on the analysis of the value creation of the organization in order to be in accordance with the organization's internal situation of the company. Organizational analysis performed in this study is through exploratory study using a qualitative approach based on the 7-S model to perform In-depthh interviews and literature review of corporate documents as the main data and using the data supporting a qualitative and quantitative research conducted by the internal and external resources of the company. The results showed that there are three variables, namely organizational skills, systems and staff that the first priority would be enhanced organizational variables. With the analysis, it can be arranged proposed Human Capital strategic initiative in creating the company's competency dictionary value.Â Keywords: Organizational Diagnosis, Business Management Competency